A carbon-based ni-mgal2o4 heterojunction electrocatalyst and a preparation method and application thereof

CN116837409BActive Publication Date: 2026-10-27ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310787729.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2026-10-27
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

[0005]针对热解制备和高温反应过程中金属原子容易迁移聚集等问题,本发明以水滑石NiMgAl LDHs为模板和自限域金属源,以邻二氮杂菲为氮源,以壳聚糖为碳源和第二氮源,提供一种碳基Ni-MgAl2O4异质结电催化剂及其制备方法,其制备过程简单、高效且所得催化剂的FECO在较宽电压范围内可维持在90%以上,同时表现出优异的催化选择性和稳定性

Benefits of technology

[0020]本发明还提供所述一种碳基Ni-MgAl2O4异质结电催化剂在CO2还原生成CO方面的应用,以负载所述碳基Ni-MgAl2O4异质结电催化剂的碳纸为工作电极,饱和银/氯化银电极为参比电极,铂片为对电极,0.5mol/L碳酸氢钾溶液为电解液,通过三电极体系进行电还原CO2反应。所述催化剂表现出优异的催化活性和选择性,在较宽还原电压范围(-0.59~-0.97V vs.RHE)内,产物CO法拉第斜率(FECO)均在90%以上,其中当还原电压为-0.82Vvs.RHE时,FECO最高可达98.33%,此时CO分电流密度(jCO)为8.9mA·cm-2。此外,该催化剂还具有优异的催化稳定性,经长时间恒电位电解,FECO和jCO基本不变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116837409B_ABST
    Figure CN116837409B_ABST
Patent Text Reader

Abstract

The application discloses a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst and a preparation method and application thereof. The electrocatalyst presents a three-dimensional nanosheet structure, has mesopore-macropore multistage pores and rich oxygen vacancies, and mainly comprises a Ni-MgAl2O4 heterojunction and nitrogen-doped carbon, wherein Ni mainly exists in the form of Ni-Nx coordination, and the presence of MgAl2O4 can inhibit the migration and aggregation of Ni monatomic atoms in the process of catalyst preparation and electrochemical reaction. The preparation method comprises the following steps: mixing NiMgAl LDHs and an ethanol solution of phenanthroline to form a solution A, mixing chitosan and an acetic acid aqueous solution to form a hydrogel B; after the solution A and the hydrogel B are mixed, the mixture is subjected to freeze drying-high temperature pyrolysis-acid etching-second heat treatment to obtain the heterojunction electrocatalyst. The preparation method is simple, low in cost and controllable, and when the electrocatalyst is applied to an electrocatalytic CO2 reduction reaction, the electrocatalyst shows high catalytic activity and CO selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy materials and electrochemistry, and relates to electrocatalytic CO2 reduction reaction. Specifically, it relates to a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst that can be used for electrocatalytic CO2 reduction reaction and its preparation method. Background Technology

[0002] Nitrogen-doped carbon-supported transition metal single-atom catalysts (MNCs), especially Ni-NCs, have become a research hotspot due to their maximized atomic utilization and excellent catalytic activity and selectivity in the electroreduction of CO2 (CO2RR) to CO production. However, the most conventional preparation method for these catalysts is currently high-temperature pyrolysis of precursors containing metal (M), nitrogen (N), and carbon (C) sources. Because metal single atoms possess very high surface energy, migration and aggregation inevitably occur during high-temperature preparation and electrochemical reactions, forming metal-based nanoparticles (MNPs) encapsulated in a carbon matrix. This reduces the single-atom catalytic selectivity and narrows the potential window for high selectivity, hindering practical applications. Therefore, effectively suppressing the migration and aggregation of metal single atoms during high-temperature preparation and reaction, and developing single-atom catalysts with high selectivity over a wide voltage range, is a key research focus and an urgent problem to be solved in the field of electrocatalysis.

[0003] Layered bimetallic hydroxides (LDHs), as a novel two-dimensional layered material, possess advantages such as the tunable composition and ratio of divalent and trivalent metal ions on the layers, and uniform distribution at the atomic level. Therefore, based on the unique advantages of LDHs as metal sources, the rational design and construction of highly efficient and selective single-atom catalysts is crucial for CO2RR research. Reference 1 (T. Zhang, et al. Angew. Chem. Int. Ed. 59 (2020) 12055-12061.) used NiCu LDHs with a Ni / Cu ratio of 9 as a precursor. After co-pyrolysis with melamine, the catalyst was successively etched with 1M hydrochloric acid and 1M nitric acid solution for 12 h, washed, and dried to obtain a nitrogen-doped carbon nanotube-supported Ni single-atom electrocatalyst coated with Ni9Cu alloy. This catalyst achieved a CO Faradaic efficiency (FE) of -0.73 V (vs. RHE). CO The highest selectivity is 97%. This catalyst is also a single-atom catalyst prepared using LDHs as templates, but its catalytic selectivity is poor over a wide voltage range.

[0004] Therefore, this invention introduces a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst with a simple preparation process and easy industrial production, and its preparation method. When applied to CO2RR, it exhibits high CO selectivity. At a reduction voltage of -0.82V vs. RHE, FE...CO Up to 98.33%, and over a wide voltage range (-0.59 to -0.97 V vs. RHE), the product FE... CO It has consistently remained above 90%. Summary of the Invention

[0005] To address the problems of easy migration and aggregation of metal atoms during pyrolysis preparation and high-temperature reaction, this invention provides a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst and its preparation method, using hydrotalcite NiMgAl LDHs as a template and a self-confined metal source, o-phenanthroline as a nitrogen source, and chitosan as a carbon source and a second nitrogen source. The preparation process is simple, efficient, and yields a catalyst with high FE... CO It can maintain above 90% over a wide voltage range, while exhibiting excellent catalytic selectivity and stability.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A method for preparing a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst uses hydrotalcite NiMgAl LDHs as a template and a self-confined metal source, o-phenanthroline as a nitrogen source, and chitosan as a carbon source and a second nitrogen source. The presence of LDHs facilitates the formation of two-dimensional nanosheet structures, while the derived MgAl2O4 inhibits the migration and aggregation of Ni single atoms during pyrolysis and the reaction process, ensuring excellent catalytic selectivity. o-phenanthroline and chitosan act as metal chelating agents and structural stabilizers, preventing the LDH sheets from stacking and agglomerating. The specific preparation steps include the following:

[0008] (1) Weigh an appropriate amount of NiMgAl LDHs and mix it thoroughly with an aqueous solution of o-phenanthroline to form solution A. Mix a certain amount of chitosan with an aqueous solution of acetic acid to form hydrosol B.

[0009] (2) After mixing solution A with hydrosol B and stirring at room temperature for 12 hours, the heterojunction electrocatalyst of the present invention is obtained by freeze drying, first heat treatment under an inert atmosphere, acid etching, and second heat treatment under an inert atmosphere.

[0010] As a preferred technical solution of the present invention, the preparation process of NiMgAl LDHs in step (1) includes dissolving a certain amount of nickel nitrate, magnesium nitrate, aluminum nitrate and urea in deionized water and mixing them thoroughly, and then obtaining NiMgAl LDHs by hydrothermal treatment, centrifugal washing and drying.

[0011] As a preferred embodiment of the present invention, the total concentration of nickel nitrate, magnesium nitrate and aluminum nitrate is 0.15 mol / L, the ratio of the total concentration of nickel nitrate and magnesium nitrate to the concentration of aluminum nitrate is 3:1, the ratio of the concentration of nickel nitrate and magnesium nitrate is 1:2 to 1:3, preferably 1:2; the ratio of the concentration of urea to the total concentration of nickel nitrate, magnesium nitrate and aluminum nitrate is (3 to 4):1.

[0012] As a preferred embodiment of the present invention, the hydrothermal reaction temperature is 120–160°C and the reaction time is 12–24 h.

[0013] As a preferred embodiment of the present invention, in step (2), the degree of deacetylation of chitosan is ≥95%, and the viscosity is 100-200 mPa·s; the mass concentration of the acetic acid aqueous solution is 1-5%, preferably 1-3%.

[0014] As a preferred technical solution of the present invention, in step (1), based on 0.5g NiMgAl LDH, the total mass of o-phenanthroline and chitosan is required to be 0.7g, and the mass ratio of o-phenanthroline to chitosan is 0.5:1 to 2.5:1.

[0015] As a preferred technical solution of the present invention, the freeze-drying temperature in step (2) is -60 to -70°C and the freeze-drying time is 8 to 12 hours.

[0016] As a preferred technical solution of the present invention, in step (2), the atmosphere of the first heat treatment is nitrogen or argon, the heating rate is 2 to 10°C / min, preferably 2 to 5°C / min; the temperature of the first heat treatment is 1000 to 1100°C; and the time of the first heat treatment is 1 to 5 hours, preferably 1 to 3 hours.

[0017] As a preferred technical solution of the present invention, in step (2), the acid etching uses 1-3 mol / L sulfuric acid, the acid etching temperature is 30-90℃, preferably 50-80℃, and the acid etching time is 3-12h, preferably 5-12h.

[0018] As a preferred embodiment of the present invention, the second heat treatment temperature in step (2) is 1000-1100℃; the heat treatment atmosphere is nitrogen or argon; the heating rate is 5-10℃ / min; and the second heat treatment time is 1-3h, preferably 1-2h.

[0019] The present invention also provides a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst prepared by the above preparation method. The catalyst exhibits a three-dimensional structure formed by nanosheets and has a mesoporous-macroporous hierarchical pore structure and abundant oxygen vacancies. It mainly includes a Ni-MgAl2O4 heterojunction and nitrogen-doped carbon, wherein Ni is supported in the carbon material in the form of Ni-Nx coordination. The presence of MgAl2O4 can inhibit the migration and aggregation of Ni single atoms during catalyst preparation and electrochemical reaction.

[0020] This invention also provides the application of the aforementioned carbon-based Ni-MgAl2O4 heterojunction electrocatalyst in the reduction of CO2 to CO. Using carbon paper supported on the carbon-based Ni-MgAl2O4 heterojunction electrocatalyst as the working electrode, a saturated silver / silver chloride electrode as the reference electrode, a platinum sheet as the counter electrode, and a 0.5 mol / L potassium bicarbonate solution as the electrolyte, the electroreduction of CO2 is carried out through a three-electrode system. The catalyst exhibits excellent catalytic activity and selectivity, with a high Faraday slope (FE) of the product CO over a wide reduction voltage range (-0.59 to -0.97 V vs. RHE). CO All were above 90%, with FE showing the highest recovery rate when the reduction voltage was -0.82V vs. RHE. CO The maximum efficiency can reach 98.33%, at which point the partial current density of CO (j CO The value is 8.9 mA·cm. -2 Furthermore, this catalyst exhibits excellent catalytic stability; after prolonged constant-potential electrolysis, FE... CO and j CO Basically unchanged.

[0021] The beneficial effects of this invention are as follows: 1. The carbon-based Ni-MgAl2O4 heterojunction electrocatalyst prepared by the method described in this invention has inexpensive and readily available raw materials, a simple and reproducible preparation process, and is easy to mass-produce, showing good prospects for industrial application. 2. By adjusting the raw material composition, heat treatment conditions, and acid etching conditions, the carbon-based Ni-MgAl2O4 heterojunction electrocatalyst prepared by the method described in this invention can yield catalytic materials with different pore sizes, oxygen vacancy concentrations, and active site numbers. The higher the oxygen vacancy concentration, the more active sites, and the better the electroreduction performance of CO2. 3. The carbon-based Ni-MgAl2O4 heterojunction electrocatalyst prepared by the method described in this invention can achieve highly selective electrocatalytic reduction of CO2 to CO in a neutral electrolyte at room temperature and pressure. Within a wide reduction voltage range (-0.59 to -0.97 V vs. RHE), FE CO All were above 90%, with the best catalytic performance observed when the reduction voltage was -0.82V vs. RHE. FE CO Up to 98.33%, j CO Up to 8.9 mA cm-2 After a long period of stability testing, FE CO and j CO Basically unchanged. Attached Figure Description

[0022] Figure 1 Scanning electron microscope image of the catalyst prepared in Example 1 of this invention.

[0023] Figure 2 Transmission electron microscopy image of the catalyst prepared in Example 1 of this invention.

[0024] Figure 3 Elemental distribution diagram of the catalyst prepared in Example 1 of this invention.

[0025] Figure 4 X-ray diffraction pattern of the catalyst prepared in Example 1 of this invention.

[0026] Figure 5 Raman spectrum of the catalyst prepared in Example 1 of this invention.

[0027] Figure 6 The adsorption-desorption isotherm curve of the catalyst prepared in Example 1 of this invention.

[0028] Figure 7 O1s XPS peak fitting diagram of the catalyst prepared in Example 1 of this invention.

[0029] Figure 8 The CO Faradaic efficiency curve of the catalyst prepared in Example 1 of this invention.

[0030] Figure 9 The CO current density curve of the catalyst prepared in Example 1 of this invention. Detailed Implementation

[0031] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above-described invention.

[0032] Example 1

[0033] The preparation method of the Ni-MgAl2O4 heterojunction electrocatalyst for the electrocatalytic CO2 reduction reaction in this embodiment is as follows:

[0034] (1) Weigh 2.6 mmol nickel nitrate, 5.2 mmol magnesium nitrate, 2.6 mmol aluminum nitrate and 35 mmol urea and dissolve them in 70 mL deionized water. The total concentration of nickel nitrate, magnesium nitrate and aluminum nitrate is 0.15 mol / L. The ratio of the total concentration of nickel nitrate and magnesium nitrate to the concentration of aluminum nitrate is 3:1. The ratio of the concentration of nickel nitrate to magnesium nitrate is 1:2. The ratio of the concentration of urea to the total concentration of nickel nitrate, magnesium nitrate and aluminum nitrate is 3.3:1. After stirring and sonicating, a mixed solution is formed. Then, the solution is hydrothermally reacted at 150 °C for 24 h. After centrifugation, washing and drying, NiMgAl LDHs are obtained. Weigh 0.5g of NiMgAl LDHs and mix it thoroughly with 10mL of o-phenanthroline aqueous solution (containing 0.4g of o-phenanthroline) to form solution A; mix 0.3g of chitosan thoroughly with 10mL of 2% acetic acid aqueous solution to form hydrosol B; the total mass of o-phenanthroline and chitosan is 0.7g, and the mass ratio of o-phenanthroline to chitosan is 4:3.

[0035] (2) After mixing and stirring solution A with hydrosol B for 12 h, freeze-drying at -60℃ for 12 h, heating to 1100℃ at a heating rate of 5℃ / min under argon atmosphere and maintaining for 2 h, cooling to room temperature, and then treating in 2 mol / L sulfuric acid solution at 80℃ for 5 h to remove Ni nanoparticles or clusters, the acid-washed product is centrifuged, washed, dried and then heat-treated again at 1100℃ for 2 h under argon atmosphere to obtain the final carbon-based Ni-MgAl2O4 heterojunction electrocatalyst.

[0036] The resulting catalyst has abundant mesopores and macropores formed by cross-linking of nanosheets, as well as abundant oxygen vacancies.

[0037] Hydrophobic carbon paper was soaked in acetone for 12 hours and then vacuum dried at 80°C for 12 hours before use. 5 mg of the prepared catalyst was weighed and added to 25 μL of 5 wt% Nafion solution and 475 μL of ethanol. The mixture was then ultrasonicated for 60 min in an ultrasonic cleaner to form a uniform catalyst ink. Then, 100 μL of the catalyst ink was dropped three times onto a 1×1 cm... 2 The catalyst loading was 1 mg / cm³ after natural drying on carbon paper. 2 The working electrodes were a saturated silver / silver chloride electrode and a platinum sheet electrode, serving as the reference and counter electrodes, respectively. A 0.5 M CO2-saturated KHCO3 solution (pH = 7.3) was used as the electrolyte. The electroreduction of CO2 was performed in a standard three-electrode H-type two-chamber electrolytic cell. The CO content in the reaction outlet gas was analyzed by gas chromatography equipped with a thermal conductivity detector (TCD) and a flame ionization detector (FID), and the CO Faraday slope and partial current density were then calculated.

[0038] Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and elemental distribution mapping (EDM) results indicate that the catalyst prepared in this embodiment exhibits a three-dimensional nanosheet structure with uniformly dispersed MgAl₂O₄ particles and a uniformly distributed Ni element. No obvious agglomeration was observed. Figure 1 , Figure 2 and Figure 3 As shown. XRD characterization results confirm that the catalyst prepared in this example mainly exhibits diffraction peaks of carbon and MgAl2O4, with no obvious diffraction peaks of metallic Ni, indirectly indicating that Ni in the catalyst is dispersed as single atoms, such as... Figure 4 As shown. Raman spectroscopy characterization results indicate that the catalyst prepared in this example has abundant defect sites, such as... Figure 5 As shown. The N2 adsorption-desorption isotherm characterization results indicate that the catalyst prepared in this example simultaneously possesses mesopores and macropores, such as... Figure 6 As shown. The XPS peak fitting results of O 1s indicate that the catalyst prepared in this example has abundant oxygen vacancies, such as... Figure 7 As shown. Electrochemical measurements indicate that the catalyst prepared in this example exhibits excellent catalytic performance for the electroreduction of CO2 to CO, with a high Faraday slope (FE) of the product CO over a wide reduction voltage range (-0.59 to -0.97 V vs. RHE). CO All were above 90%, with FE showing the highest reduction rate when the reduction voltage was -0.82V vs. RHE. CO The maximum efficiency can reach 98.33%, at which point the partial current density of CO (j CO The value is 8.9 mA·cm. -2 ,like Figure 8 and Figure 9 As shown.

[0039] Example 2

[0040] Following the preparation method of Example 1, the mass ratio of o-phenanthroline to chitosan in step (1) was adjusted to 2.5:1, while the remaining steps remained unchanged. Electrochemical performance measurements showed that when the reduction voltage was -0.82V vs. RHE, FE CO The highest possible rate is 97.21%, at which point j CO 8.28 mA·cm -2 .

[0041] Example 3

[0042] Following the preparation method of Example 1, the mass ratio of o-phenanthroline to chitosan in step (1) was adjusted to 0.5:1, while the remaining steps remained unchanged. Electrochemical performance measurements showed that when the reduction voltage was -0.82V vs. RHE, FE CO The highest possible value is 89.42%, at which point j CO 5.36 mA·cm-2 .

[0043] Example 4

[0044] Following the preparation method of Example 1, the temperatures of the first and second heat treatments in step (2) were both adjusted to 1000℃, and the remaining steps were the same as in Example 1. Electrochemical performance measurements showed that when the reduction voltage was -0.82V vs. RHE, FE CO The highest possible value is 82.7%, at which point j CO 6.99 mA·cm -2 .

[0045] Comparative Example 1

[0046] Based on Example 1, the addition of 0.4 g of o-phenanthroline and 0.3 g of chitosan in step (1) was adjusted to only 0.7 g of chitosan, with the remaining steps the same as in Example 1. Electrochemical performance measurements showed that when the reduction voltage was -0.82 V vs. RHE, FE CO The highest percentage can reach 93.61%, at which point j CO 5.66 mA·cm -2 .

[0047] Comparative Example 2

[0048] Based on Example 1, the addition of 0.4 g of o-phenanthroline and 0.3 g of chitosan in step (1) was adjusted to only 0.7 g of o-phenanthroline, with the remaining steps the same as in Example 1. Electrochemical performance measurements showed that when the reduction voltage was -0.82 V vs. RHE, FE CO The highest possible value is 80.32%, at which point j CO 2.78 mA·cm -2 .

[0049] Comparative Example 3

[0050] Based on Example 1, in step (1) only nickel nitrate is added instead of magnesium nitrate, while the remaining steps are the same as in Example 1. Electrochemical performance measurements show that when the reduction voltage is -0.77V vs. RHE, FE CO The highest rate can reach 91%, at which point j CO 3.05 mA·cm -2 .

[0051] Comparative Example 4

[0052] Following the preparation method of Example 1, the temperatures of the first and second heat treatments in step (2) were both adjusted to 1200℃, and the remaining steps were the same as in Example 1. Electrochemical performance measurements showed that when the reduction voltage was -0.82V vs. RHE, FE COIt is 68%, at which point j CO 1.6 mA·cm -2 .

[0053] Comparative Example 5

[0054] Based on Example 1, the molar ratio of nickel nitrate and magnesium nitrate in step (1) was adjusted to 1:1, and the remaining steps were the same as in Example 1. Electrochemical performance measurements showed that when the reduction voltage was -0.82V vs. RHE, FE CO The highest value can reach 47.51%, at which point j CO 0.8 mA·cm -2 .

[0055] The foregoing has shown and described the basic principles and main features of the present invention, as well as its advantages. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst, characterized in that: Using hydrotalcite NiMgAlLDHs as a template and a self-confined metal source, and o-phenanthroline as a nitrogen source, chitosan as a carbon source and a second nitrogen source, the preparation process specifically includes the following steps: (1) Mix NiMgAl LDHs with an aqueous solution of o-phenanthroline to form solution A, and mix chitosan with an aqueous solution of acetic acid to form hydrosol B; (2) Mix solution A with hydrosol B, and after the reaction is completed, freeze-dry, perform a first heat treatment under an inert atmosphere, acid etching, and perform a second heat treatment under an inert atmosphere to obtain a carbon-based Ni-MgAl2O4 heterojunction electrocatalyst. In step (1), based on 0.5 g NiMgAl LDH, the total mass of o-phenanthroline and chitosan is required to be 0.7 g, and the mass ratio of o-phenanthroline to chitosan is 0.5:1~2.5:1; In step (2), the first heat treatment atmosphere is nitrogen or argon, the first heat treatment temperature is 1000~1100℃, the heating rate is 2~10℃ / min, and the first heat treatment time is 1~5 h. In step (2), the acid etching uses 1~3 mol / L sulfuric acid, the acid etching temperature is 30~90 ℃, and the acid etching time is 3~12 h; In step (2), the atmosphere for the second heat treatment is nitrogen or argon, the temperature for the second heat treatment is 1000~1100℃, the heating rate is 5~10℃ / min, and the time for the second heat treatment is 1~3 h.

2. The method for preparing the carbon-based Ni-MgAl2O4 heterojunction electrocatalyst according to claim 1, characterized in that: The preparation process of NiMgAl LDHs in step (1) is as follows: Nickel nitrate, magnesium nitrate, aluminum nitrate and urea are dissolved in deionized water, and the total concentration of nickel nitrate, magnesium nitrate and aluminum nitrate is 0.15 mol / L. The ratio of the total concentration of nickel nitrate and magnesium nitrate to the concentration of aluminum nitrate is 3:1, the ratio of the concentration of nickel nitrate and magnesium nitrate is 1:2~1:3, and the ratio of the concentration of urea to the total concentration of nickel nitrate, magnesium nitrate and aluminum nitrate is (3~4):

1. After stirring and sonicating, a mixed solution is formed, and then hydrothermally reacted at 120~160 ℃ for 12~24 h. After centrifugation, washing and drying, NiMgAl LDHs are obtained.

3. The method for preparing the carbon-based Ni-MgAl2O4 heterojunction electrocatalyst according to claim 1, characterized in that: In step (1), the degree of deacetylation of chitosan is ≥95%, and the viscosity is 100-200 mPa.s; the mass concentration of the acetic acid aqueous solution is 1%~5%.

4. The method for preparing the carbon-based Ni-MgAl2O4 heterojunction electrocatalyst according to claim 1, characterized in that: In step (2), the stirring reaction temperature is room temperature and the stirring reaction time is 12h; in step (2), the freeze-drying temperature is -60~-70 ℃ and the freeze-drying time is 8~12 h.

5. The carbon-based Ni-MgAl2O4 heterojunction electrocatalyst prepared by any one of the preparation methods according to claims 1-4, characterized in that: The carbon-based Ni-MgAl2O4 heterojunction electrocatalyst exhibits a three-dimensional structure formed by nanosheets and has a multi-level pore structure of mesoporous and macroporous structures and abundant oxygen vacancies. It mainly consists of Ni-MgAl2O4 heterojunction and nitrogen-doped carbon, in which Ni is supported in the carbon material in the form of Ni-Nx coordination. The presence of MgAl2O4 can inhibit the migration and aggregation of Ni single atoms during catalyst preparation and electrochemical reaction.

6. The application of the carbon-based Ni-MgAl2O4 heterojunction electrocatalyst according to claim 5 in the electrocatalytic reduction of CO2 to CO, characterized in that: When the reduction voltage is -0.82 V vs When RHE, FE CO Up to 98.33%, and within -0.59 to -0.97V. vs Within the RHE voltage range, the product FE CO It has consistently remained above 90%.